Superomedial Rotation Flap: Results in Three Patients: Retalho de Rotação Súpero-Medial: Resultados em Três Doentes - Tavares, Ermelindo (Gazeta Médica, 2018)
INTRODUCTION: The superomedial rotation flap is a local randomized rotation flap that allows the closure of medium and large surgical defects in the superomedial malar region and the lower cutaneous eyelid. MATERIAL E METHODS: Two male patients and one female patient were submitted to wide excision of facial basal cell carcinoma, under local anesthesia, followed by superomedial rotation. RESULTS: There were no postoperative complications. Functional and aesthetic results were acceptable. Patients remain relapse-free at one year. DISCUSSION: Superomedial rotation is a simple procedure that is performed under local anesthesia in a single surgical period. It is an excellent option to many classical periocular surgical techniques. If well executed ectropion is an uncommon complication. CONCLUSION: Superomedial rotation was a safe and effective optional procedure in all cases.